Knee Osteoarthritis Treatment with the KineSpring Knee Implant System: A Report of Two Cases. (6th December 2012) - Hayes, David A.; Miller, Larry E.; Block, Jon E.
Abstract : Osteoarthritis (OA) is a leading cause of disability in middle-aged and older adults with the prevalence expected to increase by 40% by 2025. This dramatic projected increase in OA reflects, in large part, the alarming obesity epidemic. Indeed, it is now well understood that abnormal loading across the knee joint due to malalignment and/or excessive weight gain is responsible for accelerating OA progression. Consequently, there is a therapeutic need for alternative knee OA treatments that directly address joint overload to fill the gap between ineffective conservative care and invasive joint-modifying surgical procedures. We describe two cases that presented with bilateral knee OA resistant to conservative treatments, each with one knee previously and unsuccessfully treated with high tibial osteotomy to improve alignment and the contralateral knee successfully treated with a joint-preserving, load-absorbing implant (KineSpring Knee Implant System).